Perception of the benefits of the ownership of companion animals in people with homoerotic sexual orientation and transsexuals - Hugues H, Beatriz (2015)
The aim of this study was to become acquainted of the perception of persons with homoerotic sexual preference (HSP) (n=40) and of transsexuals (n=20) regarding pet ownership and its relationship with personal satisfaction and benefits on psicoemotional health. A survey using a questionnaire was conducted. The results showed that 83% of the persons with HSP and 85% of transsexuals were very satisfied with owning pets. Also, 98% SHO persons took more care of themselves and 93% of the transsexuals felt accompanied. In relation to the psicoemotional health 83% of HSP persons and 90% of transsexuals considered highly benefitial. It is concluded that the studied groups perceived personal satisfaction and better emotional health due to pet ownership.